Negotiating borderlines in four contemporary migrant writers from the Middle East - Tsoneva Ivanova, Petya, 1980- (Cambridge Scholars Publishing, 2018)
The book considers the persistent tendency to represent the "Middle East" as a region enclosed in less permeable boundaries. This perspective of enclosure haunts Middle Eastern Studies and is part of ongoing cultural debates on cross-border circulation, currently challenged by spectacular outbursts of violence along resurfacing lines of division. This critical study analyses selected works of four contemporary Anglophone migrant writers from the Middle East (namely, Rabih Alameddine, Diana Abu-Jaber, Laila Halaby and Elif Shafak) to demonstrate that, in spite of the forceful lines that remain after religious, ethnic and political disputes, this region does not exist as a rigidly delimited place in the writing of migrants who reclaim it back from beyond its boundaries. Rather than being a permanent location, it is constructed as a place that flows into other places and is constantly reshaped by a variety of personal stories, migrant trajectories, departures and returns